Effect of Dietary Supplementation of Amla Fruit (Emblica officinalis) Powder and Multienzyme on Growth Performance and Nutrient Utilization of Broiler Chicken - Keshav Gaur, Monika Karnani; Sheela Choudhary; Manju; Navav Singh; Geeta Choudhary (Indian Journal of Animal Nutrition, 2023)
The present study was conducted on broiler chickens to observe the effect of dietary supplementation of amla fruit powder (Emblica officinalis) and multienzyme on the growth performance, carcass characteristics, digestibility of nutrients and nitrogen balance. The feeding trial was conducted under standard feeding and managemental conditions with broiler starter (1-21days) and finisher (22-35 days) ration on one hundred and sixty; day old Ven cobb broiler chicks which were randomly divided into 4 treatment groups (T1 to T4) with four replicates of 10 chicks each. Birds were offered basal feed as per the BIS (2007). The treatment groups consisted of control group (T1) fed only with non-supplemented basal diet, group, T2 was supplemented with 0.75% amla fruit (Emblica officinalis) powder, group T3 with 0.05% multienzyme and group T4 with 0.75% amla fruit (Emblica officinalis) powder and 0.05% multienzyme in basal feed. The supplementation of amla fruit powder (Emblica officinalis) and multienzyme alone and in combination showed highly significant (P